Trends in perovskite solar cells and optoelectronics: Status of research and applications from the PSCO conference - De Angelis, F; Meggiolaro, D; Mosconi, E; Petrozza, A; Nazeeruddin, MK; Snaith, HJ (American Chemical Society, 2017)
Metal halide perovskites(1) are the subject of intensive research efforts due to the impressive performance achieved in photovoltaic and optoelectronic devices.(2, 3) The attraction toward these materials, hereafter simply perovskites, arises for a multitude of reasons. First, they show optimal primary optoelectronic properties, such as direct band gaps, long carrier diffusion lengths, and low exciton binding energies, resulting in the remarkable power conversion efficiency, over 22%, that these materials already deliver in optimized photovoltaic devices. These properites are accompanied by ease of processing via solution or vapor phase (or a combination of the two) techniques, low cost and abundance of base materials, low temperature of processing leading to versatility in terms of what substrates can be used, and the ability to process multiple layers on top of each other.